Quality Of Public Services In Pattongko Village - Nurfadillah; Zulkifli Arifin; Isna Widyawati; Mardiana (Program Studi Administrasi Publik, 2025)
This study aims to determine the quality of public services in Pattongko Village, Central Sinjai District, SinjaiRegency. The approach in this study uses a type of research in the form of literature study or literature study. The data analysis technique used in the research uses the content analysis method which can be used to obtain valid information and can re-examine it according to its context. The results of this study indicate that the quality of public services in Pattongko Village is quite good which is characterized by several factors. Where the employees have expertise or skills in each different field. For example, in the Family Card (KK) making section, the employees are able to serve the community well. The service facilities are also good, where the Pattongko Village Office, Sinjai Tengah kec.sinjai in making Family Cards is now via online, namely via Whatsup (WA). In this service access also provides adequate physical access so as to facilitate the service process of employees to residents.